2014
DOI: 10.5005/jp-journals-10024-1527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Mitotic Figures in Oral Epithelial Dysplasia using Crystal Violet and Feulgen Stain

Abstract: Background: Routine staining procedures often pose a problem in differentiating a mitotic cell from an apoptotic cell, deteriorating the reliability of histology grading. Although various new methods have been recommended for identifying mitotic figures (MFs) in tissues, the time factor and cost makes them less feasible. Thus, an attempt was made to evaluate the efficacy of crystal violet and Feulgen reaction in identifying MFs and also to see for any variation in the number of MFs in various grades of Epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Similarly, Rao et al also noted a significant increase in the number of MFs in Feulgenstained sections as compared to 1% crystal violetstained samples. 10 A similar study by Palaskar et al evaluating the effectiveness of H&E, toluidine blue, Giemsa, crystal violet and Feulgen stains in oral epithelial dysplasia samples concluded that all of the aforementioned stains were useful in the identification of MFs, although Feulgen stains yielded superior results. 19 In a study evaluating oral epithelial dysplasia and OSCC, Nikita et al reported that Feulgen stains provided a greater contrast when staining MFs as compared to H&E, toluidine blue, Giemsa and crystal violet stains; in addition, the MFs were easier to see at lower magnifications in comparison to the other stains.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly, Rao et al also noted a significant increase in the number of MFs in Feulgenstained sections as compared to 1% crystal violetstained samples. 10 A similar study by Palaskar et al evaluating the effectiveness of H&E, toluidine blue, Giemsa, crystal violet and Feulgen stains in oral epithelial dysplasia samples concluded that all of the aforementioned stains were useful in the identification of MFs, although Feulgen stains yielded superior results. 19 In a study evaluating oral epithelial dysplasia and OSCC, Nikita et al reported that Feulgen stains provided a greater contrast when staining MFs as compared to H&E, toluidine blue, Giemsa and crystal violet stains; in addition, the MFs were easier to see at lower magnifications in comparison to the other stains.…”
Section: Discussionmentioning
confidence: 93%
“…The Feulgen stain is a modified histochemical stain that is simple, cost-effective, reliable and allows for differentiation between apoptotic bodies, karyorrhexis and MFs, thereby excluding false-positive results. 2,5,10,11 Furthermore, the purple-coloured chromatin material against a green cytoplasm facilitates the identification of MFs, even at lower magnifications. Multiple studies have reported using Feulgen staining to study nuclear and cellular morphometry and chromatin frameworks in oral cytosmears or paraffin-embedded tissue sections of various potentially malignant lesions, such as oral hyperplasia, dysplasia and OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Special stains like gallocyanin, Nissl stain, Giemsa and toluidine blue, Feulgen have also been employed for studying mitotic figures. 9,13,35 Switching over to a modified histochemical stain that is cost effective and statistically reliable in its potential would be a wise option and Crystal Violet proved to be promising in this regard.…”
Section: Discussionmentioning
confidence: 99%